Investigation of important parameters for Photo-Fenton degradation of methyl orange over Fe/TiO2 catalyst - Pongsert Sriprom; Witthaya Krobthong; Pornsawan Assawasaengrat (Energy Reports, 2020)
Methyl orange (MO) is an intensely colored compound used in dyeing and printing textile, which contaminates the effluent. Photo-Fenton reaction is one of the advanced oxidation processes (AOPs) which can treat the pollutant to the green products and small molecules. Photo-Fenton process using Fe/TiOcatalyst was applied to decolorization of methyl orange. The Fe/TiO2 catalyst was prepared by using dry impregnation method. Plackett-Burman Full Factorial was applied to identify the significant parameters in methyl orange decolorization. Six factors (i.e. Fe/TiO2 catalyst concentration, initial O2 concentration, initial MO concentration, pH, stirring speed, and light intensity) influencing methyl orange decolorization were investigated. The results showed that the regression model for parameter screening was well-fitted with the experiment data, supported by the high R2 of 0.95. The results also showed that Fe/TiO2 catalyst dosage, O2 concentration, initial MO concentration, stirring speed, and light intensity were the significant effects (P < 0.05) rather than pH. The assumption means a lot in engineering design involving with the confounding multifactor. It could be seen from the conclusion that Plackett-Burman Full Factorial is a suitable tool for screening a large number of parameters, when the complicating interactions of these parameters are involved. Therefore, the key parameters can be found and properly engineered; thus warranting the treatment efficiency and minimizing the cost.
Keywords: 330; Photo-Fenton process; Methyl orange; Fe/TiO2 catalyst; Plackett-Burman Full Factorial Design